ASPEK BIOTEKNIK DALAM PEMANFAATAN SUMBERDAYA IKAN TERI DI PERAIRAN PALABUHANRATU KABUPATEN SUKABUMI - Diniah, Diniah; Sobari, Moch. Prihatna; Primadianti, Indah (Jurnal Teknologi Perikanan dan Kelautan, 2017)
The research objective to lay open aspects of technique and bio-technique in optimal anchovy resources utilization in Palabuhanratu water in order to anchovy resources can be exploited on the responsible fisheries condition. Its calculation is done to use approach Clark, Yoshimoto and Pooley (CYP), Walter-Hiborn (W-H) and Fox Algorithm models. This research use time series data from 1997 until 2007. The result show that the construction of bagan rakit in Palabuhanratu water consisted of the bagan house, bagan net, anjang-anjang and roller. In its operational, they use 6 units of carrosene lamps. During period 1997 to 2007, amount of unit and effort of bagan rakit to tend to increase, while production of anchovy tend to decrease and increasing to productivity of bagan rakit. Mean of actual production of anchovy resources 30.48 tons per year and actual effort is 26,816 trips per year. Estimation model of anchovy resources management in Palabuhanratu water appropriate Fox Algorithm model, with of static optimal production of equal to 38.51 tons per year and optimal effort of equal to 32,049 trips per year. Result of calculation at period 1997 to 2007 indicating that anchovy resources utilization in Palabuhanratu water can be categorized not yet degraded and biological over fishing.